Construction of a binary architecture of flower-like nickel phyllosilicate@zinc sulfide towards the robust, wear-resistant and thermal-stable epoxy nanocomposites. (January 2023) - Yang, Ji-nian; Li, Zhen-yu; Feng, Xue-song; Nie, Shi-bin
Highlights: A binary architecture of NiPS@ZnS was facilely constructed. An adequate amount of as-synthesized NiPS@ZnS can be dispersed well in EP matrix. The introduced NiPS@ZnS enhanced the strength and modulus of EP moderately. The friction coefficient was rarely changed while the wear rate decreased significantly. NiPS@ZnS could make EP nanocomposites more thermally stable but decreased the energy barrier during thermal decomposition. Abstract: In the present study, a binary architecture of flower-like nickel phyllosilicate decorated using zinc sulfide nanoparticles (NiPS@ZnS) was constructed and introduced into epoxy resin (EP), yielding the robust, wear-resistant and thermal-stable nanocomposites. Several characterizations have been performed to confirm the synthesis of target NiPS@ZnS and explore its positive influence on the mechanical, tribological and thermal properties of EP nanocomposites. Based on the results, NiPS@ZnS could be dispersed homogeneously in the matrix without visible occurrences of debonding between interfaces, moderately improving the tensile strength and elastic modulus by 11.4% and 24.6%, respectively. The optimized tribological properties were achieved by adding 5% NiPS@ZnS and the wear rate could be reduced significantly down to 0.5×10 −5  mm 3 /Nm, which was ca . 93% lower than pure EP. Thermal degradation analysis implied that presented NiPS@ZnS improved the thermal stability, showing pronounced suppressed mass loss and elevated char residues, while kinetic analysis demonstrated the rarely changed reaction order and steadily decreased activation energy of EP along with the increased NiPS@ZnS. This investigation provided a facile way to prepare the robust, wear-resistant and thermal-stable EP-based tribo-materials. Graphical abstract: A series of epoxy (EP) nanocomposites involving varied mass fractions of NiPS@ZnS binary architectures were prepared. Owing to the excellent synergistic effects between NiPS nanoflowers and ZnS nanoparticles, giant improvements in the wear resistance and thermal stability of EP nanocomposites were exhibited. By adding 5% of NiPS@ZnS, the wear rate decreased by 93% regarding pure resin. Image, graphical abstract